Protective effect of nimodipine against cerebral injury induced by subacute carbon monoxide intoxication in mice - Yang Jun-Qing; Zhou Qi-Xin (Acta Pharmacologica Sinica, 2016)
Aim: To study the effects of nimodipine on delayed cerebral injury in mice from subacute carbon monoxide (CO) exposure. Methods: Mice were exposed to CO (100 mL/kg, ip) once a day, continuously for 7 d. After 7-d CO-exposure, mortality in mice, changes in learning ability and memory using passive avoidance test, the pathomorphologic observation of brain tissue slices, and changes of monoamine oxide (MAO)-B activities in cerebral tissue were studied. Nimodipine was administered 30 min before CO-exposure every time. Results: The preadministration of nimodipine decreased the mortality in mice, almost reversed the impairment of learning and memory function, prevented the hippocampal neurons against delayed death and blunted the rise of MAO-B activity after subacute CO poisoning of mice. Conclusion: Pretreatment with nimodipine markedly prevented mice from delayed encephalopathy after CO poisoning.